The novel mandiangin - yani, sur (Lingual Journal of Language and Culture; Vol 7 No 1 (2019): Lingual: Journal of Language and Culture, 2019)
Novel Mandiangin has been approved and published in a book that has 142 pages written by Hary B, Koriun is a literary work in 2008. In this novel tells the story of the destruction of a village that can reap a valuable lesson from this novel mainly lies in disappointment and injustice. In the academic, field the lessons of this novel are more centered on harmony among the people. the narrative style used in the Mandiangin novel is quite unique and different from the others, such as the narrative used is structured starting from ancient times onwards. The use of symbolism in the novel Mandiangin is more about the combination of language between Malay and Indonesian. The prominent reason for reviewing this novel is because so that this novel can give us an impression and it is very interesting to review more about the ins and outs of this novel.